(untitled) (ESMAT Magazine, 2023)
This research consists of a content analysis on the jurisprudence of the Superior Electoral Court (TSE) related to disinformation. The aim of the study was to analyze how the TSE is delimiting its jurisprudence regarding disinformation in the Brazilian electoral process, freedom of expression and the abuse of power resulting from the mass use of this disinformation. For theoretical contextualization, the phenomenon of disinformation and freedom of expression was discussed, as well as the abuse of power in its three forms: political, economic and abuse in the use of the media. In the development of the work, we observed greater concentration for issues on freedom of expression followed by the themes of abuse of economic power and abuse of power by the misuse of the media. For the subject of abuse of political power, there was a single case, but emblematic.